Pengaruh Atribut Perusahaan terhadap Pengungkapan Sustainability Report - Putri, Anggie Wiyan; Marsono, Marsono (STIE Widya Manggala, 2025)
This research aims to examine the influence of profitability, firm age, firm size, industrial type, and audit committee on the disclosure of sustainability reports. The data used is secondary data obtained from annual reports and sustainability report LQ45 companies listed on the Indonesian Stock Exchange (IDX) during 2020 - 2023. The sample selection method used was purposive. The data analysis technique used is multiple linear regression test. The results showed that profitability, firm size, and industrial type have a positive and significant influence on the disclosure of sustainability reports. The audit committee variable has a negative influence on the disclosure of sustainability reports. The firm age variable does not affect the disclosure of sustainability reports.